A alimentação como processo de integração da comunidade Árabe em Foz do Iguaçu - Santos, Clenise Maria Reis Capellani dos (2013)
The Syrian Lebanese immigration to Brazil started in the late XIX century, it crossed decades, persisted through the XXI century, reaching Foz do Iguaçu in the mid 50 s as peddlers, who ventured into the countryside in search of newopportunities. Once settled here, attracted by the opportunities, they took roots the triple border region, thus determining a long-standing relationship with the city. This thesis addresses how to evaluate this community s feeding as an integration process of this community, presenting some reflections about the uses and appropriations of the Arab culture eating habits into the city of Foz do Iguaçu. The research was carried out through structured interviews, in addition to books, newspapers, dissertations, and Internet portals. The structure is composed of three chapters, starting a discussion about the Arab immigration and on the reasons why this expansion has determined their arrival in Brazil and to Foz do Iguaçu, as well as the community habits peculiarities brought into the border region; in sequence a historical report on the Arab cooking and food culture is made, recalling its origin from farmers in order to demonstrate their current eating habits; finalizing with how the eating habits of origin are preserved, and how the city embodies this rich cuisine. The Arab cuisine, as observed, is a combination of art, cultural Brazilian exchanges and beyond. The adaptation of the dishes is facilitated by the city s multiculturalism. Tradition and creation compose a junction of stories through the dishes, seasonings, religion and culture among others, where the relationship between past and present strengthens the building of a flexible and negotiated identity, and demonstrates that among the present ethnic groups in the city, the Arab culture delineates with evidence its social space.